2001
DOI: 10.1038/sj.onc.1204311
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oral squamous epithelial lesions: are they genetically related?

Abstract: The development of second primary tumors (SPTs) in patients with head and neck squamous cell carcinoma (HNSCC) has become an increasingly important factor in clinical treatment decison. Currently, clinical and histologic parameters are used to determine whether or not SPT is present. Recent studies suggest that many SPTs in the upper aerodigestive tract have a common clonal origin, challenging the longstanding multiclonal origin concept. To determine genetic relationships among multiple oral cancerous and prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…We have previously demonstrated that multiple oral premalignant lesions may be the result of the spreading of index lesions in some patients. 16 It would also be interesting to investigate whether podoplanin is involved in such process. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that multiple oral premalignant lesions may be the result of the spreading of index lesions in some patients. 16 It would also be interesting to investigate whether podoplanin is involved in such process. …”
Section: Discussionmentioning
confidence: 99%
“…72 As mentioned above, the majority of studies investigating multifocal urothelial lesions have demonstrated a monoclonal origin. However, there are several studies indicating that field cancerization contributes to urothelial p53, p53 gene mutation analysis; FISH, fluorescence in situ hybridization; MSI, detection of high-grade microsatellite instability using the Bethesda primer panel 76 and immunohistochemistry of mismatch repair proteins (oligoclonality was presumed only if 1 clone exhibited high-grade instability and the other did not).…”
Section: Oligoclonality and Field Cancerizationmentioning
confidence: 99%
“…[38][39][40][41] The multifocal nature of early oral carcinogenesis may hinder local treatment modalities. 7,37,38,42 In a recent study, we have demonstrated that cancer developed in the same location as did the preceding leukoplakia in 79% (37) of the 47 oral cancer patients.…”
Section: Multifocality Of Oral Carcinogenesismentioning
confidence: 99%